Nano-Hydroxyapatite Gel and Its Effects on Remineralization of Artificial Carious Lesions - Apa Juntavee; Niwut Juntavee; Ainaj Nuñez Sinagpulo (International Journal of Dentistry)
Introduction. Nano-hydroxyapatite gel (NHG) has never been investigated for enamel remineralization. This study evaluated the effects of two concentrations of NHG on remineralization of an artificial carious lesion in comparison with nano-HA toothpaste (NHT) and fluoride varnish (FV). Materials and Methods. Carious lesions were prepared on 100 enamel samples and divided into 5 groups: FV, NHT, 20% NHG, and 30% NHG. One untreated (NT) group was left as control. The hardness of the surface was evaluated before, during, and after remineralization. Microhardness at various phases and the percent recovery of hardness (%HR) were determined and analyzed with ANOVA. Polarized-light micrographs (PLM) were evaluated for depth of the carious lesion. Results. Significantly different remineralization capability was indicated for tested agents (p<0.05). NHT was significantly capable of remineralization greater than NHG, FV, and NT (p<0.05). No noticeable difference in %HR between 20% NHG and 30% NHG (p>0.05) was found. Decreasing in the depth of caries lesion was notified by PLM as applying either NHT or NHG as greater than FV, with no reduction in the depth for NT. Conclusions. Nano-HA both in toothpaste and gel form was capable of remineralization better than fluoride varnish. Comparable remineralization of 20% versus 30% NHG was evidenced. NHG for both concentrations was recommended as a capable remineralizing agent for caries remineralization. Clinical Significance: This study indicated that an application of nano-HA gel is an attractive route to deliver the material and can be more effective and less toxic than conventional formulations and provide its effectiveness directly at the site of action, especially for a noncooperative young child and medicinally intimidated patients who may face with inconvenience in using toothbrush and toothpaste for hygiene control.